2000
DOI: 10.1177/014572170002600210
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promotion Practices of Young Black Women at Risk for Diabetes

Abstract: A systematic approach of planning and actively incorporating health-promoting activities into one's lifestyle as a young adult may protect or delay the onset of diabetes and prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…The instrument is a 48-item 4-point Likert scale that measures the frequency of health promoting behaviors in six subscales, which include health responsibility, exercise, nutrition, interpersonal relationships, stress management, and spiritual growth. The instrument has been used in minority and Caucasian populations (Jefferson, Melkus, & Spollett, 2000) and is available in English and Spanish. Alpha co-efficients range from 0.92 for the entire scale and from 0.70 to 0.90 for the subscales.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The instrument is a 48-item 4-point Likert scale that measures the frequency of health promoting behaviors in six subscales, which include health responsibility, exercise, nutrition, interpersonal relationships, stress management, and spiritual growth. The instrument has been used in minority and Caucasian populations (Jefferson, Melkus, & Spollett, 2000) and is available in English and Spanish. Alpha co-efficients range from 0.92 for the entire scale and from 0.70 to 0.90 for the subscales.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Most chronic diseases have a nutritional component. For example, risk factors for the development of diabetes are obesity and inactivity (Jefferson et al 2000). Additionally, a diet high in saturated fat increased the risk for heart disease, and colorectal cancer (Weisburger, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Jefferson et al (2000) found a mean score on HPLP II health responsibility of 2.59 +.59, HPLP II Spiritual respectively. The scores on health responsibility in the study by Jefferson (Jefferson et al, 2000) were similar to those found in the present study. However, the women in the present study scored higher on Spiritual Growth and Interpersonal Relations.…”
Section: Research Question 5: What Is the Interrelationship Of Spiritmentioning
confidence: 94%
“…A study comparing the lifestyles of obese and non-obese African American and European American women in a southern city used a two-by-two comparative description design (Nies et al, 1998 In yet another study, the health promoting practices of Black women at risk for diabetes were examined (Jefferson et al, 2000). consistent with a plethora of research on the diet and exercise practices of African American women.…”
Section: Health Promoting Lifestyle Profilementioning
confidence: 99%
See 1 more Smart Citation